Efectividad de los métodos de colocación de implantes odontológicos - García Manzano, Fátima Rocío (2019)
Dental implant placement methods are a great progress in the scientific and useful field with successful results, currently used in professional practice by dentists to make implant treatment a reliable and successful procedure. The present work seeks to evaluate the effectiveness of dental implant placement methods through a systematic review of the literature considering different techniques that the professional uses to carry out implant treatment in patients who have partial or total edentulous spaces. The bibliographic search was carried out in databases such as PubMed, Google Scholar, SciELO and Elsevier during the period 2008-2018, applying inclusion criteria and exclusion criteria; filters such as the Average Count Citation (ACC) and the Scimago Journal Raking (SJR), thus obtaining a total of 60 articles. As a result of the literature review, it was obtained that the preoperative planning methods for implant placement is a very important step to reach the success of the treatment and to guide the professional during the procedure. The conventional method is planned through the use of panoramic x-ray, study models and conventional surgical guides; while in the guided method, assisted by a computer the planning is more rigorous based on panoramic radiographs, study models, CT scans, CAD CAM and surgical guides assisted by a computer. While the planning of the placement methods is more rigorous, the treatment is more likely to be successful in the short and long term